2017
DOI: 10.1016/j.neuropharm.2017.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Two delta opioid receptor subtypes are functional in single ventral tegmental area neurons, and can interact with the mu opioid receptor

Abstract: The mu and delta opioid receptors (MOR and DOR) are highly homologous members of the opioid family of GPCRs. There is evidence that MOR and DOR interact, however the extent to which these interactions occur in vivo and affect synaptic function is unknown. There are two stable DOR subtypes: DPDPE sensitive (DOR1) and deltorphin II sensitive (DOR2); both agonists are blocked by DOR selective antagonists. Robust motivational effects are produced by local actions of both MOR and DOR ligands in the ventral tegmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 75 publications
0
35
0
Order By: Relevance
“…Furthermore, the formation of MOR-DOR heteromers in native tissue may be both cell-dependent and systemdependent. 18,40 Demonstration of a unique pharmacologic profile is one of the key requirements for recognition of heteromer formation in native systems. 41,42 Several observations outlined in this study indicate that MOR and DOR are unlikely to function as a heteromer in the ENS.…”
Section: Lack Of Evidence For Heteromerization Of Mor and Dor In The Ensmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the formation of MOR-DOR heteromers in native tissue may be both cell-dependent and systemdependent. 18,40 Demonstration of a unique pharmacologic profile is one of the key requirements for recognition of heteromer formation in native systems. 41,42 Several observations outlined in this study indicate that MOR and DOR are unlikely to function as a heteromer in the ENS.…”
Section: Lack Of Evidence For Heteromerization Of Mor and Dor In The Ensmentioning
confidence: 99%
“…In this study, MOR-induced hyperpolarization was enhanced in the presence of selective DOR antagonists. 40 However, this may be an overinterpretation because there was a population of myenteric neurons that expressed only MOR or DOR. Therefore, we used additional approaches to examine whether MOR-DOR heteromers exist in the colon.…”
Section: Lack Of Evidence For Heteromerization Of Mor and Dor In The Ensmentioning
confidence: 99%
“…Super-saturating concentrations of the MOR selective agonist DAMGO (10 μM) or the DOR selective agonist DPDPE (10 μM) were pressure ejected onto VTA neurons in the same manner as U-69,593. We have previously shown that DAMGO and DPDPE responses in VTA neurons in acute brain slices do not desensitize [3,4]. In responsive neurons, the agonist was re-applied after 10 nM of either KOR antagonist had been bath applied for at least 4 min.…”
Section: Resultsmentioning
confidence: 99%
“…In the ventral tegmental area where the two receptors functionally interact, increased G protein dependent K + conductance in response to DPDPE or deltorphin II was observed in the presence of the mu antagonist CTAP. Conversely the delta antagonist TIPPψ enhanced DAMGO evoked responses (Margolis et al 2017) suggesting that mu-delta functional interactions blunt this signalling pathway in vivo.…”
Section: Activation Of Endogenous Mu-delta Heteromers Promotes Sustaimentioning
confidence: 99%
“…In VTA slices, co-application of the delta antagonist TIPPψ together with the mu agonist DAMGO or co-application of the mu antagonist CTAP together with the delta agonists deltorphin II or DPDPE strongly suggested that mu-delta receptor heteromerization decreases opioid signal transduction (Margolis et al 2017). In addition, constitutive recruitment of βarrestin 2 by mu-delta heteromers was observed in SKNSH neuroblastoma cells that affected ERK1/2 signaling ).…”
Section: Introductionmentioning
confidence: 99%